Regulatory Gaps in Bitcoin Inheritance under Indonesian Civil and Islamic Law - Qurrotaaini, Qonita Syamila (Program Studi Hukum Keluarga Islam, 2026)
This study examines the legal status of Bitcoin as inheritable property under the Indonesian Civil Code and Islamic law amid increasing digital asset ownership in Indonesia. Despite its growing use, no specific legal framework governs Bitcoin inheritance, creating uncertainty regarding digital wallet access, ownership verification, private key transfer, and the protection of heirs’ rights. This research employs a normative legal method using statutory, conceptual, and comparative approaches based on primary, secondary, and tertiary legal materials. The findings indicate that Bitcoin may be classified as inheritable property because it constitutes intangible movable property under the Indonesian Civil Code and satisfies the concepts of al-māl and māl mutaqawwam in Islamic law. However, the absence of procedural regulations governing digital asset inheritance continues to undermine legal certainty and effective inheritance administration. This study contributes to the development of Indonesian inheritance law by proposing a normative framework for regulating Bitcoin inheritance and recommending comprehensive legal provisions to ensure legal certainty and stronger protection for heirs in the digital era.